2010
DOI: 10.1021/ic101229p
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ligand Substitution on the Exchange Interactions in {Mn12}-Type Single-Molecule Magnets

Abstract: We investigate how ligand substitution affects the intramolecular spin exchange interactions, studying a prototypical family of single-molecule magnets comprising dodecanuclear cluster molecules [Mn(III)(8)Mn(IV)(4)O(12)(COOR)(16)]. We identify a simple scheme based on accumulated Pauling electronegativity numbers (AEN) of the carboxylate ligand groups (R). The redistribution of the electron density, controlled by the AEN of a ligand, changes the degree of hybridization between 3d electrons of manganese and 2p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…However, it may be that J varies in a much more complicated manner within the deformation range in which the model applies. For example, it is known that J also depends on the Mn-O-Mn angles in various MMs [47] and the entire structure of the ligand connecting the two spins [37]. In a future study we will extract the functional form of J from detailed first-principles calculations, and also consider applying similar mathematical approaches to the design of molecules with other highly functional properties.…”
Section: Discussion and Final Remarksmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it may be that J varies in a much more complicated manner within the deformation range in which the model applies. For example, it is known that J also depends on the Mn-O-Mn angles in various MMs [47] and the entire structure of the ligand connecting the two spins [37]. In a future study we will extract the functional form of J from detailed first-principles calculations, and also consider applying similar mathematical approaches to the design of molecules with other highly functional properties.…”
Section: Discussion and Final Remarksmentioning
confidence: 99%
“…the superexchange mechanism through the oxygen atoms [34,35]) or how the coupling strengths are affected by the molecular structure of the MM (e.g. the organic groups attached to the O atoms in Mn 12 -type molecules [36,37]). Spin Hamiltonian models are therefore potentially useful if we are strictly interested in predicting MMs with interesting magnetic properties, such as robustness of the total spin under molecular shape deformations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Mn 12 molecules have been synthesized with various ligands, and prior studies have showed that magnetic properties and exchange interactions of a SMM are strongly R-dependent. [13][14][15][16][17][18][19] To understand the effect of physical environment on properties of SMMs, especially that of a supporting substrate, it is desirable to place Mn 12 on well-defined surfaces and investigate the electronic and magnetic properties of individual molecules and monolayers. Much effort has already been made to deposit Mn 12 on various substrates, such as the metal Au(111), 20,21 the semi-metal Bi(111), 22 and even the ferromagnetic substrate Ni(111).…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that properties such as size and electronegativity of the substituents in the ligands influence strongly the degree of p-d hybridization, thus the electronic structure of the SMMs. 7,8 Furthermore, incorporation of the additional functional groups into carboxylate ligands can lead to formation of Mn 12 O 12 CR assemblies through various kinds of molecule interactions. 9 The supramolecular SMM dimer [Mn 4 O 3 Cl 4 (EtCO 2 ) 3 ( py) 3 ] 2 held together by close intermolecular Cl⋯Cl contact and C-H⋯Cl hydrogen bonds shows quantum magnetic behavior different from that of the discrete SMMs.…”
Section: Introductionmentioning
confidence: 99%